Identifying It Governance and Management Objectives (GMO) With COBIT 2019: Case Study Islamic State University Ar-Raniry - Venita Ananda; Ghufran Ibnu Yasa; Ima Dwitawati (Elkawnie, 2025)
Abstract: The alignment of IT governance with institutional strategies plays a vital role in improving educational services, innovation, professionalism, collaboration, and communication. This study examines IT governance at UIN Ar-Raniry using the COBIT 2019 framework, with a qualitative approach analyzing documents outlining the institution's vision, mission, goals, and strategies. The analysis identifies client service/stability as the priority design factor, focusing on fostering a customer-oriented service culture while addressing critical risks in data and information management. Key challenges include duplication of initiatives, insufficient IT resources, inadequate staff skills, staff dissatisfaction, outdated systems hindering new initiatives, and poor data quality and integration. To address these challenges, 14 prioritized Governance and Management Objectives (GMOs) were identified from COBIT 2019's 40 sub-domains, including EDM02 (Ensure Benefits Delivery), EDM04 (Ensure Resource Optimization), APO02 (Manage Strategy), APO05 (Manage Portfolio), BAI01 (Manage Programs and Projects), and DSS01 (Manage Operations). These GMOs aim to guide IT governance efforts, optimize resources, address organizational inefficiencies, and improve overall performance. This framework is anticipated to enable UIN Ar-Raniry to effectively create value through IT implementation, ensuring alignment with its strategic goals and addressing its most pressing governance issues. Abstrak: Tata elola teknologi informasi (TI) yang selaras dengan strategi institusi memainkan peran penting dalam meningkatkan layanan pendidikan, inovasi, profesionalisme, kolaborasi, dan komunikasi. Penelitian ini menganalisis tata kelola TI di UIN Ar-Raniry menggunakan kerangka kerja COBIT 2019, dengan pendekatan kualitatif yang menganalisis dokumen visi, misi, tujuan, dan strategi institusi. Hasil analisis mengidentifikasi client service/stability sebagai prioritas dari desain faktor strategi, dengan tingkat kepentingan tujuan yaitu pada pengembangan budaya layanan yang berorientasi pada pelanggan, serta mengatasi risiko utama dalam pengelolaan data dan informasi. Beberapa tantangan utama yang dihadapi meliputi duplikasi inisiatif, keterbatasan sumber daya TI, kurangnya keterampilan staf, ketidakpuasan staf, sistem yang sudah usang sehingga menghambat inisiatif baru, serta kualitas dan integrasi data yang buruk. Untuk menangani tantangan tersebut, diperoleh 14 Governance and Management Objectives (GMO) yang diprioritaskan diidentifikasi dari 40 sub-domain COBIT 2019, termasuk EDM02 (Ensure Benefits Delivery), EDM04 (Ensure Resource Optimization), APO02 (Manage Strategy), APO05 (Manage Portfolio), BAI01 (Manage Programs and Projects), dan DS501 (Manage Operations). Keempat belas GMO ini dirancang untuk memandu upaya tata kelola TI, mengoptimalkan sumber daya, mengatasi ketidakefisienan organisasi, dan meningkatkan kinerja institusi secara keseluruhan. Kerangka kerja ini diharapkan mampu mendukung UIN Ar-Raniry menciptakan nilai melalui penerapan TI yang efektif serta memastikan keselarasan dengan tujuan strategis dan pengelolaan isu tata kelola yang paling mendesak.